2002
DOI: 10.1016/s0960-9822(02)01125-9
|View full text |Cite
|
Sign up to set email alerts
|

The Gibberellin Pathway Mediates KNOTTED1-Type Homeobox Function in Plants with Different Body Plans

Abstract: We suggest that repression of GA activity by KNOX transcription factors is a key component of meristem function. Transfer of the KNOX/GA regulatory module from the meristem to the leaf may have contributed to the generation of the diverse leaf morphologies observed in higher plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
395
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(423 citation statements)
references
References 46 publications
23
395
0
5
Order By: Relevance
“…Furthermore, application of GA 3 or 1-NAA resulted in exclusion of all three KNOX proteins from the nucleus. It has been shown that KNOX gene expression in the SAM represses the activity of a GA biosynthetic enzyme, GA20-oxidase, implicating that increased GA production can occur in the leaf primordia where KNOX gene expression is down-regulated (Sakamoto et al, 2001;Hay et al, 2002Hay et al, , 2004. Therefore, our observation that GA 3 induces the nuclear exclusion of KNOX proteins fits well with our hypothesis that regulation of nuclear localization could represent a safety mechanism to ensure tight control of KNOX activity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, application of GA 3 or 1-NAA resulted in exclusion of all three KNOX proteins from the nucleus. It has been shown that KNOX gene expression in the SAM represses the activity of a GA biosynthetic enzyme, GA20-oxidase, implicating that increased GA production can occur in the leaf primordia where KNOX gene expression is down-regulated (Sakamoto et al, 2001;Hay et al, 2002Hay et al, , 2004. Therefore, our observation that GA 3 induces the nuclear exclusion of KNOX proteins fits well with our hypothesis that regulation of nuclear localization could represent a safety mechanism to ensure tight control of KNOX activity.…”
Section: Discussionsupporting
confidence: 90%
“…Transcription factors involved in SAM organization include the KNOX class-1 homeodomain proteins, which have been named after the maize protein KNOTTED1 (KN1) and are involved in maintenance of the undifferentiated state of stem cells Endrizzi et al, 1996;Brand et al, 2002). It has been proposed that the process of SAM maintenance depends on inhibition of gibberellin (GA) biosynthesis through down-regulation of GA20-oxidase by KNOX proteins (Kusaba et al, 1998;Sakamoto et al, 2001;Hay et al, 2002Hay et al, , 2004. In addition, interactions between KNOX genes and other plant hormones appear to be involved (Hamant et al, 2002;Scanlon, 2003;Hay et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…SAM regulators from the KNOTTED1-like homeobox (KNOXI) protein family were shown to induce expression of the cytokinin-biosynthesis gene ISOPENTENYL TRANSFERASE7 and accumulation of the hormone in the meristem (Jasinski et al, 2005;Yanai et al, 2005). Proteins from this family were also shown to negatively control GA level in the SAM by binding to the GA20ox promoter and directly repressing its transcription (Sakamoto et al, 2001;Hay et al, 2002;Chen et al, 2004). KNOXI and cytokinin both induced the expression of the gene encoding the GA-deactivating enzyme GA2ox at the base of the SAM, perhaps to block biologically active GAs transported to the SAM from flanking tissues (Jasinski et al, 2005).…”
Section: Reciprocal Interaction Between Ga and Cytokininmentioning
confidence: 99%
“…Cytokinins, which positively regulate cell division (RiouKhamlichi et al, 1999;Howell et al, 2003;Ferreira and Kieber, 2005), are required for meristem function and maintenance (Giulini et al, 2004;Leibfried et al, 2005;Kurakawa et al, 2007). GAs and auxin act antagonistically to cytokinins with GAs promoting cell differentiation (Chien and Sussex, 1996;Ogas et al, 1997;Perazza et al, 1998;Hay et al, 2002) and auxin promoting organ initiation (Reinhardt et al, 2000). Cytokinin signaling in plants is similar to the bacterial two-component phosphorelay system composed of a His kinase sensor and a response regulator.…”
mentioning
confidence: 99%